تأثير عناصر التقوية من النوع I على متانة الألواح المقواة في السفن - أحمد, غالب; عيسى, هيثم; يوسف, علي (Latakia University Journal -Engineering Sciences Series, 2019)
Stiffened panels form the main structure of ship's hull. These panels are founded in the bottom structure ,side shell , deck and bulkhead .The stiffened panels consist of Plates , Beams and Girders which located in transvers and longitudinal directions . Panels subject to different loads so that the stiffeners are been to resist these loads . When designing a definite area of stiffened panels , the dimensions of stiffeners and the distance between them constitute in reducing the weight of panels and the cost of constructions .The effect of stiffener dimensions and the distance between them on the strength of panels , are studied The aim of this research is to define the lightest weight of panels with remaining on the necessary strength of panels. تشكل الألواح المقواة الإنشاء الرئيسي لبدن السفينة, فهي توجد في إنشاءات القاع, الغلاف الجانبي, السطوح والقواطيع. تتألف الألواح المقواة من ألواح وعوارض تشكل عناصر التقوية . تتعرض الألواح للأحمال , فتقوم عناصر التقوية بمقاومة هذه الأحمال . ترتب عناصر التقوية على الألواح في الاتجاهات الطولية والعرضية. تعتبر أبعاد عناصر التقوية والمسافة بينها مهمة جداً عند تصميم مساحة محدودة من اللوح المقوى , كونها تساهم في توفير الوزن وتكاليف الإنشاء. سيتم في هذا البحث دراسة تأثير أبعاد عناصر التقوية من النوع I , والمسافة بين هذه العناصر على متانة اللوح المقوى , وذلك بهدف الوصول إلى اللوح المقوى الأقل وزناً مع المحافظة على المتانة الضرورية للوح.